2011
DOI: 10.1074/jbc.m111.226100
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Analogue Excision and Discrimination Modulated by Mutational Complexes Including Single Amino Acid Deletions of Asp-67 or Thr-69 in HIV-1 Reverse Transcriptase

Abstract: Single amino acid deletions in the ␤3-␤4 hairpin loop of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) have been identified in heavily treated patients. The deletion of Asp-67 together with mutations T69G and K70R (⌬67 complex) are usually associated with thymidine analog resistance mutations (TAMs) (e.g. M41L, T215Y, etc.) while the deletion of Thr-69 (⌬69) is rarely found in isolates containing TAMs. Here, we show that the complex ⌬67/T69G/K70R enhances ATP-dependent phosphorolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Following selection with TDF and EFdA, virtually all the resultant variants contained D67del, T69G and K70R (Table 3). Previous studies have reported that D67del alone has little effects on HIV-1's sensitivity to AZT, but the addition of T69G and K70R confers significant AZT resistance, designating these three aberrant changes as the 'delta 67 complex' [32][33][34][35]. In the present study, the delta 67 complex reduced the activity of TDF by a factor of 83 (Table 5).…”
Section: P0supporting
confidence: 54%
“…Following selection with TDF and EFdA, virtually all the resultant variants contained D67del, T69G and K70R (Table 3). Previous studies have reported that D67del alone has little effects on HIV-1's sensitivity to AZT, but the addition of T69G and K70R confers significant AZT resistance, designating these three aberrant changes as the 'delta 67 complex' [32][33][34][35]. In the present study, the delta 67 complex reduced the activity of TDF by a factor of 83 (Table 5).…”
Section: P0supporting
confidence: 54%
“…Recombinant infectious viruses were generated as we described previously [27,28]. Briefly, 100 ng of fulllength protease or 500 ng of gag purified PCR products were cotransfected into MT-4 cells with 1 μg of protease-deleted [29] or gag-protease-deleted [30] HXB2 clone that had been previously linearized with BstE II (New England Biolabs).…”
Section: Generation Of Synthetic Hiv-1mentioning
confidence: 99%
“…The indel positional matrix had a bonus score of 6 for RT codon 69. There have been two other well-described regions with indels in these HIV-1 genes: deletions in the RT β3-β4 loop region [ 4 , 8 ] and insertions between codons 33 and 41 in protease [ 9 ]. NucAmino did not include scores for these in the indel positional matrix, because each of the RT β3-β4 loop deletions are associated with different drug-resistance interpretations and because the protease codon 33/41 insertions are not associated with drug resistance.…”
Section: Methodsmentioning
confidence: 99%